DISCURSO NA COLAÇÃO DE GRAU DO CURSO DE ARQUITETURA E URBANISMO UEG/ UnUCET / TURMA 2-2012 (Revista Plurais (e-ISSN 2238-3751), 2013)
DISCURSO NA COLAÇÃO DE GRAU DO CURSO DE ARQUITETURA E URBANISMO UEG/ UnUCET / TURMA 2-2012